Unraveling the functional instability of bacterial consortia in crude oil degradation via integrated co-occurrence networks - Li, Ping; Liang, Xiaolong; Shi, Rongjiu; Wang, Yongfeng; Han, Siqin; Zhang, Ying (Frontiers in Microbiology, 2023)
Soil ecosystems are threatened by crude oil contamination, requiring effective microbial remediation. However, our understanding of the key microbial taxa within the community, their interactions impacting crude oil degradation, and the stability of microbial functionality in oil degradation remain limited. In this study, we enriched a crude oil-degrading bacterial consortium generation 1 (G1) from contaminated soil, achieving a total petroleum hydrocarbon (TPH) degradation rate of 32.29% within 10 days. Through three successive transfer passages, G2-G4 consortia were established, resulting in a gradual decrease in TPH degradation to 23.14% at the same time.Specifically, saturated hydrocarbon degradation rates ranged from 18.32% to 14.17% among G1-G4, and only G1 exhibited significant aromatic hydrocarbon degradation (15.59%). Functional annotation based on PICRUSt2 and FAPROTAX showed that functional potential of hydrocarbons degradation diminished across generations. These results demonstrated the functional instability of the bacterial consortium in crude oil degradation. Integrated Co-occurrence Networks method was used to analyze microbial species correlation with crude oil components across G1-G4. The relative abundance of the Dietzia genus showed the highest positive correlation with the degradation efficiency of TPH and saturated hydrocarbons (19.48, 18.38, p < 0.05, respectively), Bacillus genus demonstrated the highest positive correlation (21.94, p < 0.05) with the efficiency of aromatic hydrocarbon degradation. The key scores of Dietzia genus decreased in successive generations. A significant positive correlation (16.56, p < 0.05) was observed between the Bacillus and Mycetocola genera exclusively in the G1 generation. The decline in crude oil degradation function during transfers was closely related to changes in the relative abundance of key genera such as Dietzia and Bacillus as well as their interactions with other genera including Mycetocola genus. Our study identified key bacterial genera involved in crude oil remediation microbiome construction, providing a theoretical basis for the next step in the construction of the oil pollution remediation microbiome.